Efficacy and safety of decitabine combined with HAAG (homoharringtonine, aclarubicin, low-dose cytarabine and G-CSF) for newly diagnosed acute myeloid leukemia - Zhu, Jun-Feng; Dai, Hai-Ping; Zhang, Qian-Qian; Yin, Jia; Li, Zheng; Cui, Qin-Ya; Tian, Xiao-Peng; Liu, Si-Ning; Jin, Zheng-Ming; Zhu, Xia-Ming; Wu, De-Pei; Tang, Xiao-Wen (Frontiers in Oncology, 2022)
The 7+3 regimen is the front-line induction chemotherapy in patients with newly diagnosed acute myeloid leukemia, with a response rate of 60-80%. But it’s not suitable for all patients especially old/unfit patients because of a higher treat related mortality. Therefore, more safer and effective induction therapies are required. In this retrospective study, 50 patients with acute myeloid leukemia were received decitabine combined with HAAG(homoharringtonine,aclarubicin, low-dose cytarabine and G-CSF) as induction therepy. Complete remission(CR) rate was 96% (48/50) and ORR was 100%. Of note, 6 ( /6) patients harboring FLT-ITD mutation all achieved CR. The median OS was 40.0 months (range 2.0, 58.0). The OS of 1, 3, and 5 years were 75.3%, 54.2%, and 49.3%. The median RFS was 38.0 months (range 2.0, 58.0). The RFS of 1, 3, and 5 years were 67.3%, 48.9%, and 45.1%. The OS and RFS of patients who received hematopoietic stem cell transplatation (HSCT) consolidation was significantly better than that of patients who did not receive HSCT (P=0.017;0.016). The incidence of grade 3-4 neutropenia and thrombocytopenia was 84% and 88%. The incidence of grade 3-4 infection and bleeding was only 16% and 6%. There was no early death. In conclusion, DAC+HAAG regimen is effective and well-tolerated as induction therapy in patients with newly diagnosed AML.